Hubungan Pemberian Tablet Zinc dengan Durasi Diare pada Balita di Wilayah UPT Puskesmas Cinere Kota Depok - Yuniar Kusumawardani (2020)
In Indonesia, diarrhea is still the cause of infant mortality. Government Tablet. The benefits of zinc can help the process of improvement in pushing food. From this study to analyze zinc tablets with the duration of diarrhea in infants. Disable this research using Cross-Sectional. The technique used in taking the sample is accidental sampling with a sample of 75 toddlers. Data is collected by a questionnaire distributed online using the help of Google forms. This study uses the Rank Spearman correlation test. From 75 respondents the average delivery of zinc tablets for 6 days and from 75 respondents the average duration of diarrhea in children for 3 days. There was a contribution of zinc tablets with a duration of diarrhea in infants with p values (0.027). It can be concluded that more and more mothers are giving zinc tablets to toddlers of diarrhea can reduce the level of duration of diarrhea in toddlers. This research suggests more assistance in giving zinc tablets to be more compliant and can support research results.